Peran Pesantren Dalam Mendukung Tercapainya Sustainable Development Goals Dengan Pengelolaan Sampah Berbasis Bank Sampah (Studi Pondok Pesantren Darussalam Blokagung Banyuwangi) - El Madaniya, Nadiya (ITB AAS INDONESIA Surakarta, 2024)
Sustainable development (SDGs) is a big agenda compiled by the United Nations which has 17 goals, one of which is to reduce waste. The waste problem is currently serious. The more people who are active, the more waste is generated. The solution to handling the waste problem must be good management. One of them is the waste bank program. The waste bank is a program that utilizes sorted waste. The waste bank system is similar to the bank system, but what is stored is dry waste that can be recycled. This study aims to see Islamic boarding schools' role in supporting SDG achievement through waste management programs. In addition, the purpose of this study is the impact of a waste bank on the Islamic boarding school environment. This study uses a qualitative approach. The discussion of this research is based on the results of observations and interviews with waste bank management. The results of this study are in a positive direction that the existence of a waste bank at least helps and supports sustainable development and also that this waste bank activity provides an example to students on how to manage waste properly and correctly. However, the obstacle is that not all students are aware of this. So that the impact of a waste bank activity has been running until now but not too significant.